Catalan Nationalism: Past and Present - Kirill A. Mamaev (Ибероамериканские тетради, 2017)
The article dissects the problem of Catalan Nationalism. The author analyzes the historical development of Catalan nationalist movement. The article examines the relations between Spain and Catalonia up to the present time and makes attempts to propose the resolution of this problem.